Intervenção precoce: programa de leitura para crianças com e sem autismo - Muller, Katia Fabiane (2021)
The scientific literature reveals the promising effects of Dialogic Reading (DL) on the reading comprehension of children with typical and atypical development. Studies also point to the effectiveness of involving primary caregivers as intervention agents in treating children with autism. This study aimed to evaluate the effects of a reading program that employs Dialogic Reading (DL) principles on the reading comprehension of a 3-year-old child with Autism Spectrum Disorder (ASD) and a 4-year-old with typical development. Using a quasi-experimental intra-subject research design, the effects of a DL protocol, employed by the mothers, on the children's responses were evaluated. The study was carried out at the residence of the dyads. Autoscopy was used as a training strategy for caregivers, who learned to use the proposed DL protocol. The results revealed that: (a) caregivers learned to implement the protocol with their children; (b) children with typical development showed an increase in the frequency of correct answers and interaction initiatives; (c) the child with autism became more responsive; and (d) the protocol was positively evaluated by the caregivers. Adaptations to the protocol as well as its limitations are discussed.